Материалы к фауне комаров-лимониид (Diptera, Limoniidae) СССР. Подсемейство Eriopterinae, род Mesocyphona O.-S. - Савченко, Е.Н. (Вестник зоологии, 1972)
The genus Mesocyphona 0.-S. is represented in the fauna of the Soviet Union by six species. The following three are described as new:
Mesocyphona spinifera S а v. sp. n.— Маle. General coloration yellow. The flаgellar segments of antennae brownish-black. Mesonatal praescutum blackish-brown, the humeral regions yellowed. Pleura bistriped by brown. Wings unicolorous, without distinct stigma. Abdomen clear yellow with brown dorsal stripe. Hypopyg is figured (Fig. 2). Bodv length near 3.0 mm, wing— 4.0 mm. Fem a l e like to the male. Body length near 3.3 mm, wing 4.3 mm. Terra typica — the Tuva Autonomous SSR.
Mesocyphona conica S av. sp. n.— Very similar to the M. spinifera. Differs in all features of the male hypopyg structure, especially by the IX tergite and aedeagus (Fig. 3). Body length near 3.5 mm, wing— 4.0 mm. Fem a l e similar to the male. Terra typica — the Azerbaijan SSR.
Mesocyphona lilliputina Sa v., sp. n.— General coloration yellow. Antennae distally darkened. Mesonotal praescutum greyish, very indistinct striped with brownish. Wings unicolorous. Hypopyg is figured (Fig. 4). Body length near 2.5 mm, wing— 3.0 mm. F e m a l e unknown. Terra typica — the Tajik SSR.
Due to the male hypopyg characters Rhgpholophus bivittatus L w. is attributed to the genus Mesocyphona O.-S. (comb. nov.).